2016
DOI: 10.3892/etm.2016.3387
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional contrast-enhanced magnetic resonance angiography for anterolateral thigh flap outlining: A retrospective case series of 68 patients

Abstract: Flap transfer is increasingly used for repairing limb defects secondary to trauma or tumor, and appropriate preoperative planning plays a critical role. The present study aimed to examine the use of three-dimensional (3D) contrast-enhanced magnetic resonance angiography (CE-MRA) in evaluating the blood supply distribution and perforating branch pattern of anterolateral thigh (ALT) flaps. Bilateral donor lower limbs were scanned in 68 patients (136 limbs) using a Siemens Avanto 1.5 T magnetic resonance imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…By contrast, C-CTA provided a satisfactory mapping efficiency, which was higher than that of T-CTA and any previously reported values. 6,8,12,19,22 Notably, by using the C-CTA technique, we report promising results for demonstrating the presence of perforators, especially the most used perforators (type B) and the most difficultto-detect perforators (type C). 6 More importantly, C-CTA could accurately predict the origin and course if the perforator was detected successfully.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…By contrast, C-CTA provided a satisfactory mapping efficiency, which was higher than that of T-CTA and any previously reported values. 6,8,12,19,22 Notably, by using the C-CTA technique, we report promising results for demonstrating the presence of perforators, especially the most used perforators (type B) and the most difficultto-detect perforators (type C). 6 More importantly, C-CTA could accurately predict the origin and course if the perforator was detected successfully.…”
Section: Discussionmentioning
confidence: 81%
“…Most importantly, preoperative mapping information has been sought as a profound strategy to influence surgeons to optimize the reconstructive strategy and thus maximize operative success. 5,[8][9][10] Almost all available imaging modalities have been proposed for the preoperative evaluation of perforators, 5,11 including hand-held Doppler (HHD), color duplex sonography (CDS), digital subtraction angiography (DSA), computed tomography angiography (CTA), and magnetic resonance angiography (MRA). Regarding the accuracy, there is emerging evidence supporting the use of CTA as a preferred method.…”
mentioning
confidence: 99%
“…We found that the microvessels of the distal areas had reappeared and that the tissue edema was reduced in the RIPC group. Although longer times are needed to process and measure the perforator arteries with a 3D model, CTA has been widely used to imagine the locations and paths of perforating vessels for flap harvest and transfer, since it can yield much more information than the two‐dimensional CT scans (Jiang et al, 2016; Smit et al, 2010). Here, the results were consistent with the above observation that the imaging of the microvessels and their branches are more clearly observed in flap subjected to RIPC.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Additional disadvantages of digital subtraction angiography include its radiation exposure and inability to visualize muscles, nerves, and fat. 16 , 18 Radiation exposure is also a limitation of CTA, which has been used to visualize the ALT in other studies. 10 …”
Section: Introductionmentioning
confidence: 99%